2020
DOI: 10.5205/1981-8963.2019.243643
|View full text |Cite
|
Sign up to set email alerts
|

O manejo da sífilis gestacional no pré-natal

Abstract: Objetivo: analisar o manejo da sífilis gestacional durante a assistência pré-natal. Método: trata-se de um estudo bibliográfico, tipo revisão integrativa, desenvolvido por meio de uma pesquisa sistemática na BVS com os descritores em saúde, nas bases de dados LILACS, MEDLINE e BDENF durante o mês de junho. Selecionaram-se artigos originais na íntegra; em português, inglês e espanhol; publicados entre 2017 a 2019. Utilizou-se o CASP para análise de elegibilidade dos estudos, apresentando-os em forma de figuras … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
(13 reference statements)
0
3
0
3
Order By: Relevance
“…In this regard, it is important to note that the strengthening of primary health care services, by expanding the coverage of the family health strategy and building attention networks, brought greater qualification of care, expanding the monitoring through the assignment of the territory and linkage with the team and making the diagnosis of diseases more accessible to the population 6 , 9 . However, some challenges are still present, such as the high percentage of cases with inadequate treatment regimens and the low rate of concomitant treatment of the partner, observed in this study and reported in the literature 8 .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In this regard, it is important to note that the strengthening of primary health care services, by expanding the coverage of the family health strategy and building attention networks, brought greater qualification of care, expanding the monitoring through the assignment of the territory and linkage with the team and making the diagnosis of diseases more accessible to the population 6 , 9 . However, some challenges are still present, such as the high percentage of cases with inadequate treatment regimens and the low rate of concomitant treatment of the partner, observed in this study and reported in the literature 8 .…”
Section: Discussionmentioning
confidence: 66%
“…As for the treponemal test, besides the three previous factors, death was also a predictor of greater chances of reactivity. The protective factor related to syphilis diagnosis at the time of delivery is related to the identification of treponema before the disease is activated in the newborn and without complications for the mother 8 . This is why it is essential to carry out the rapid test at the time of delivery, even if the pregnant woman has already been tested in the last trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Segundo os dados apresentados nesse estudo é constatado que houve uma notificação crescente da notificação de SG, outros estudos como de Cunha et al ( 2020) e Cavalcante et al ( 2017) também apontam tendências de crescimento da doença no país. O aumento dos números de casos pode ser resultado da mudança na definição de casos, que também passou a levar em consideração os casos de sífilis no parto e no pós-parto, como também no aumento da disponibilidade de teste rápido e o fortalecimento dos sistemas de vigilância em saúde, ainda assim, devido ao grandes casos de subnotificação de doenças que ocorrem no Brasil, o real número de casos pode ser maior (Rosa, et al, 2020). Autores como Saraceni et al (2017) apontam que esse crescimento é preocupante, pois apesar do avanço tecnológico para o diagnóstico e tratamento para a SG, o seu controle se estende como um grande desafio para a atenção ao pré-natal.…”
Section: Discussionunclassified
“…Tal fato ocorre pela falta e dificuldade da realização dos diagnósticos e falha na notificação de cada caso identificado. Com base em estudos, a deficiência no acompanhamento pré-natal é um fator determinante para o agravamento de casos, pois faz com que sejam perdidas chances de realizar uma adequada avaliação e tratamento materno, uma vez que o diagnóstico adequado da sífilis gestacional é o diferencial para que possa haver um controle significativo da SC (Rosa et al, 2020).…”
Section: Introductionunclassified